2014
DOI: 10.1186/ar4533
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic assessment reveals detailed distribution of synovial inflammation in Blau syndrome

Abstract: IntroductionArthritis is the most frequent manifestation of Blau syndrome, an autoinflammatory disorder caused by the genetic mutation of NOD2. However, detailed information on arthritis in Blau syndrome on which the therapeutic strategy should be based on is lacking. This multi-center study aimed to accurately characterize the articular manifestation of Blau syndrome and also to demonstrate the utility of musculoskeletal ultrasound in Blau syndrome.MethodsPatients who had been diagnosed with Blau syndrome by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In regard to pathophysiology, the effects of NOD2 mutations are not extensively known and remain somewhat ambiguous. After the first clinical reports on the disease [4,[30][31][32][33], and the discovery of NOD2 locus [38] and its mutations [46,52], more significant contributions to the knowledge of BS and EOS have come from case reports or illustrative case series [99] and international registries [60,64,72]. The rarity and heterogeneity of BS and EOS have not allowed for the determination of treatment guidelines, therefore prospective clinical trials are clearly needed in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In regard to pathophysiology, the effects of NOD2 mutations are not extensively known and remain somewhat ambiguous. After the first clinical reports on the disease [4,[30][31][32][33], and the discovery of NOD2 locus [38] and its mutations [46,52], more significant contributions to the knowledge of BS and EOS have come from case reports or illustrative case series [99] and international registries [60,64,72]. The rarity and heterogeneity of BS and EOS have not allowed for the determination of treatment guidelines, therefore prospective clinical trials are clearly needed in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Normocytic anemia can occur as expression of chronic systemic inflammation [85]. Vascular inflammation involves large vessels [47,99], and Takayasu arteritis has been reported both in the familial [89] and sporadic forms of disease [88]. Arterial hypertension has often been described [60,72].…”
Section: Systemic Manifestations Can Be Proteanmentioning
confidence: 97%
See 1 more Smart Citation
“…Soft tissue swelling can occur due to inflammation in the intra‐articular synovium and tenosynovium. However, joint destruction is not commonly reported …”
Section: Discussionmentioning
confidence: 99%
“…In Ikeda’s study, ultrasound was used to assess the swollen joints in ten patients with Blau syndrome [ 35 ]. These authors reported a high proportion of involved joints presenting with tenosynovitis rather than intra-articular synovitis (41.5% versus 27.9%).…”
Section: Genetic Classification With Clinical and Imaging Findingsmentioning
confidence: 99%